Thermal gradient effects on steel I-girders in bridges: A review - Naqvi, Syed Muhammad Oan; Ali Zaidi, Syed Hussain (Journal of Engineering and Sciences, 2025)
Steel I-girders in bridges experience thermal gradients induced by environmental factors, which generate non-uniform stresses, resulting in deformation, fatigue, and dynamic impacts, causing reduced service life. This review consolidates the numerical, experimental, and field-measured data-based studies to examine the effects of thermal gradient stresses on steel I-girder in bridges, emphasizing gaps in current design approaches, such as their limited focus on transverse thermal effects and nonlinear temperature gradients. Key outcomes highlight that both vertical and transverse thermal effects often exceed the values assumed in bridge design codes, with transverse stresses contributing significantly to the overall stress of curved bridges. Finite element analysis methods realistically simulate these thermal effects. Advanced sensors in field measurements, such as Fiber Bragg Grating systems, highlight the importance of location-specific thermal profiles. This review advocates adaptive design strategies, including advanced thermal models, optimized girder geometries, and flexible bearing placement to minimize and deal with thermal stresses.